THE USE OF THREE-STEP INTERVIEW TECHNIQUE ON STUDENTS’ SPEAKING ABILITY - Ricky Aditya Pratama; Abdul Rosyid; Entis Sutisna (Pedagogia: Jurnal Ilmiah Pendidikan, 2021)
Teaching speaking is one of the important parts of foreign language learning. The ability to communicate in a second language is a key to the success of the learner to master English language and to his success in their real life. The fact that cannot be denied is that sometimes students feel reluctant to speak because of shyness and fear of making a mistake. Three-step Interview technique is one of the techniques from cooperative learning that has many positive effects. This research is conducted to find out the effect of using Three-Step Interview technique on students’ speaking ability. It is conducted online at Pakuan University. In this research, a pre-experimental method with one group pre-test and post-test is used. There are 30 students in the first semester as samples. The data are taken from pre-test and post-test. Some steps are done to analyse the data and the design of the t-test formula is applied to get the final result. Based on the data calculation, it shows the t-test value is 19.7. The results of t-test and t-table with d.f = 29 at significant level 0.05 is 2.04. It shows that t-test value is higher than t-table (19.7 greater than 2.04). It means that the alternative hypothesis is accepted. In conclusion, there is an effect of using a three-step interview technique on students’ speaking ability.